Circular Dichroism in Biological Photonic Crystals and Cubic Chiral Nets - Saba, Matthias; Thiel, M.; Turner, M. D.; Hyde, S. T.; Gu, Min; Grosse-Brauckmann, K.; Neshev, D. N.; Mecke, Klaus; Schröder-Turk, Gerd (Physical Review Letters, 2011)
Nature provides impressive examples of chiral photonic crystals, with the notable example of the cubic so-called srs network (the label for the chiral degree-three network modeled on SrSi2) or gyroid structure realized in wing scales of several butterfly species. By a circular polarization analysis of the band structure of such networks, we demonstrate strong circular dichroism effects: The butterfly srs microstructure, of cubic I4(1)32 symmetry, shows significant circular dichroism for blue to ultraviolet light, that warrants a search for biological receptors sensitive to circular polarization. A derived synthetic structure based on four like-handed silicon srs nets exhibits a large circular polarization stop band of a width exceeding 30%. These findings offer design principles for chiral photonic devices.